2019
DOI: 10.4314/gjl.v8i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Ideologies and Impoliteness Strategies in Online Ethno-Religious Conflict Among Nigerians

Abstract: Nigeria is a multilingual country comprising peoples of different ethnic, political and religious inclinations, hence the incessant ethno-religious conflicts that lace her trajectory. Different scholarly works have examined ethno-religious conflict in the Nigerian space from the religious, sociological, historical and political perspectives. However, little attention has been given to the phenomenon from the linguistic perspective. This study, therefore, drawing inputs from van Dijk's Critical Discourse Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Existing studies have documented adequate evidence of the connection between impoliteness and online discursive culture (Blitvich 2010;Neurauter-Kessels 2011;Angouri/Tseliga 2012;Sinkevicuite 2018). Such studies based on the Nigeria context have identified different forms of impoliteness in online discourses in Nigeria (Taiwo 2014;Oyebade 2018;Ajayi/Bamgbose 2019;Taiwo 2020). Oyebade (2018) is partly similar to this study in the sense that it investigated politeness in asynchronous computer mediated discourse in Nairaland Forum.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have documented adequate evidence of the connection between impoliteness and online discursive culture (Blitvich 2010;Neurauter-Kessels 2011;Angouri/Tseliga 2012;Sinkevicuite 2018). Such studies based on the Nigeria context have identified different forms of impoliteness in online discourses in Nigeria (Taiwo 2014;Oyebade 2018;Ajayi/Bamgbose 2019;Taiwo 2020). Oyebade (2018) is partly similar to this study in the sense that it investigated politeness in asynchronous computer mediated discourse in Nairaland Forum.…”
Section: Introductionmentioning
confidence: 99%